Memanen Hujan: Proyek Kolaboratif Penguatan Profil Pelajar Pancasila (P5) Gaya Hidup Berkelanjutan - Thomas Dannar Sulistyo; Yoga Jati Kusuma; Nikolas Noel Ferdiansyah (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2025)
This best practice aims to design a collaborative learning approach integrating Geography, Mathematics, and Chemistry through the Pancasila Student Profile Strengthening Project (P5) under the theme Sustainable Lifestyle. The subjects of this best practice were 199 students from classes X1–X6 at Kolese De Britto Senior High School during the second semester of the 2023/2024 academic year. The collaborative learning process was conducted in five stages: (1) engagement, (2) exploration, (3) transformation, (4) presentation, and (5) reflection. Student responses to the project were collected via Google Forms. Data analysis was carried out by reducing data from the questionnaires, presenting it in qualitative and quantitative forms, and drawing conclusions. The P5 collaborative project consisted of five stages: rainfall data collection (rain harvesting), data processing, rainwater filtration and distillation, infographic creation, and evaluation-reflection. Rain harvesting was identified as the most challenging stage (30.8%), while the filtration and distillation stage was seen as needing the most improvement (43.6%). This project resulted in increased knowledge, skills, and the application of values aligned with the Pancasila Student Profile. Skills that improved through this collaborative learning included processing rainfall data (85.5%), collaborating in rainfall data collection (71.8%), analyzing rainfall data (70.9%), and collaborating in infographic creation (59.8%). The project also raised awareness about the importance of clean water and the health impacts of pollution, while motivating students to care more about the environment through concrete actions.